2017
DOI: 10.1039/c6ra28634h
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of a magnetic self-healing poly(vinyl alcohol) composite hydrogel

Abstract: This study proposes a simple method to fabricate a magnetic self-healing poly(vinyl alcohol) (ms-PVA) composite hydrogel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Moreover, while polymer/nanosheet composites have been vigorously studied [ 74 , 75 ], no combination between a synthetic gelator and an inorganic nanosheet has yet been reported for such a thixotropic gel except for our previous report on a LMWG/ inorganic nanosheet system. In relation to this study, facile preparation processes of magnetic composite polymer hydrogels composed of iron oxide particles and poly(vinyl alcohol) have been reported in the literature [ 76 78 ].
Scheme 1.
…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while polymer/nanosheet composites have been vigorously studied [ 74 , 75 ], no combination between a synthetic gelator and an inorganic nanosheet has yet been reported for such a thixotropic gel except for our previous report on a LMWG/ inorganic nanosheet system. In relation to this study, facile preparation processes of magnetic composite polymer hydrogels composed of iron oxide particles and poly(vinyl alcohol) have been reported in the literature [ 76 78 ].
Scheme 1.
…”
Section: Introductionmentioning
confidence: 99%
“…The result is quite similar to that in Ding's literature . It can be concluded that the surface centered cubic magnetic Fe 3 O 4 particles were successfully fabricated and the XRD patterns don't show any other peaks, which illustrated the samples have a high purity and great degree of crystallinity . In addition, the prominent peaks in XRD patterns of the pure Fe 3 O 4 NPs are poignant and high.…”
Section: Resultsmentioning
confidence: 89%
“…[45] It can be concluded that the surface centered cubic magnetic Fe 3 O 4 particles were successfully fabricated and the XRD patterns don't show any other peaks, which illustrated the samples have a high purity and great degree of crystallinity. [46] In addition, the prominent peaks in XRD patterns of the pure Fe 3 O 4 NPs are poignant and high. However, when it comes to the XRD patterns of Fe 3 O 4 @NVP-DVB NPs (Figure 3b, c), the corresponding peaks turn to plain and lower compared with peaks of Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19-06290), confirming the successful preparation of the magnetic Fe 3 O 4 particles. [17] As can be seen from Figure 2…”
Section: Introductionmentioning
confidence: 79%